Roald Hoffmann on the philosophy, art, and science of chemistry - Hoffmann, Roald (Oxford University Press, 2012)
"Roald Hoffmann's contributions to chemistry are well known; this Nobel laureate has published more than 500 articles and two books. As an "applied theoretical chemist," he has made significant contributions to our understanding of chemical bonding and reactivity, and taught two generations of chemists how to use molecular orbitals for real chemistry. Less well known, however, are Hoffmann's important and insightful contributions to the areas of scholarship surrounding chemistry. Over a career that spans nearly fifty years, Roald Hoffmann has thought and written copiously about the broader context of chemistry and its relationship to the arts and poetry. This book contains Hoffmann's essays and is organized around several major themes: chemical reasoning and explanation, writing and communicating in science, ethics, art and science, and chemical education. A few are unpublished lectures that are valuable additions to the volume. The editors have the full cooperation of Roald Hoffmann in this project. Most of the published work will be reprinted verbatim, but a few of the essays will be revised to eliminate redundancy. The unpublished lectures will also be edited since they were originally intended to be delivered orally at specific occasions. The editors will provide an introduction to the book, and some introductory material for each section. In introducing the material, they will highlight the intrinsic importance and interest of the ideas, as well as the places where Hoffmann's thought makes novel contributions to cognate areas"--